Pathogenesis of parkinsoys disease. Microvascular and neurochemical analysis. - Rafael, Hernando (1996)
Contrary to the hypothesis of genetic predisposition in the pathogenesis of Parkinson discase as proposed by many researchers, we suggest that an impairment of blood flow to the substantia nigra is the primary pathological process of this disease, not necessarily related to aging. Conclusion: Based ¡n histopathological and neurochenfical findings ¡n dopaminergic neurons, Parkinson's discase is due to a suboptinial and chronic reduction of arteria¡ blood flow to the mesencephalon. Therefore, revascularization of the catecholaminergic nuclei is an aim to be considered.